Underground Asia global revolutionaries and the assault on Empire - Harper, Timothy N. 1965- (Belknap Press of Harvard University Press, 2021)
"This is the epic tale of how modern Asia emerged out of conflict between imperial powers and a global network of revolutionaries in the turbulent early decades of the twentieth century. In 1900, European empires had not yet reached their territorial zenith. But a new generation of Asian radicals had already planted the seeds of their destruction. They gained new energy and recruits after the First World War and especially the Bolshevik Revolution, which sparked utopian visions of a free and communist world order led by the peoples of Asia. Aided by the new technologies of cheap printing presses and international travel, they built clandestine webs of resistance from imperial capitals to the front lines of insurgency that stretched from Calcutta and Bombay to Batavia, Hanoi, and Shanghai. Tim Harper takes us into the heart of this shadowy world by following the interconnected lives of the most remarkable of these Marxists, anarchists, and nationalists, including the Bengali radical M. N. Roy, the iconic Vietnamese leader Ho Chi Minh, and the enigmatic Indonesian communist Tan Malaka. He recreates the extraordinary milieu of stowaways, false identities, secret codes, cheap firearms, and conspiracies in which they worked. He shows how they fought with subterfuge, violence, and persuasion, all the while struggling to stay one step ahead of imperial authorities. Underground Asia shows for the first time how Asia's national liberation movements crucially depended on global action. And it reveals how the consequences of the revolutionaries' struggle, for better or worse, shape Asia's destiny to this day."--
Keywords: Kommunistische Internationale; Geschichte 1905-1927; Anarchismus; Revolutionär; Unabhängigkeitsbewegung; Asien; Asia / History / Autonomy and independence movements; Asia / History; Autonomy and independence movements; Asia; History